Cysteine‐Rich Antifungal Proteins from Filamentous Fungi are Promising Bioactive Natural Compounds in Anti‐Candida Therapy. Issue 5 (20th February 2019) - Galgóczy, László; Yap, Annie; Marx, Florentine
Abstract: The emerging number of life‐threatening invasive fungal infections caused by drug‐resistant Candida strains urges the need for the development and application of fundamentally new and safe antifungal strategies in the clinical treatment. Recent studies demonstrated that the extracellular cysteine‐rich and cationic antifungal proteins (crAFPs) originating from filamentous fungi, and de novo designed synthetic peptide derivatives of these crAFPs provide a feasible basis for this approach. This mini‐review focuses on the global challenges of the anti‐ Canidia therapy and on the crAFPs as potential drug candidates to overcome existing problems. The advantages and limitations in the use of crAFPs and peptide derivatives compared to those of conventional antifungal drugs will also be critically discussed. Abstract :